Policing the COVID-19 Pandemic: Exploratory Study of the Types of Organizational Changes and Police Activities Across the Globe - Maskály, Jon (International criminal justice review, 2021)
The COVID-19 pandemic upended major facets of global society, including policing. This study describes three types of changes that police agencies in counties worldwide made. First, how have various domains of policing changed and how much did they change? Second, were these changes regulated by the official policy? Third, what are the potential consequences of the changes made during the pandemic? Taking a mixed-methods approach, our quantitative survey data from 27 countries, buttressed by qualitative responses, enable us to examine changes in these three areas. Our results suggest there is a great deal of heterogeneity in the degree of change, the use of policy to make the changes, and the perceived effects of the changes. Some changes (i.e., the use of personal protective equipment) are relatively ubiquitous and common sense based on the pandemic. Other organizational changes show a great deal more variation, especially when considering the valence of the change. Finally, the police executives from these countries express a highly optimistic—and potentially overly rosy—view of the potential longer term consequences of the pandemic or the operational changes made because of it. Overall, the results paint a more complicated picture of the responses to the pandemic made by the police organizations included in our sample. We conclude by discussing the implications of these findings for future research, police practice, and the development of policy.